Influence of Flaxseed Lignan Supplementation to Older Adults on Biochemical and Functional Outcome Measures of Inflammation. (17th November 2017) - Di, Yunyun; Jones, Jennifer; Mansell, Kerry; Whiting, Susan; Fowler, Sharyle; Thorpe, Lilian; Billinsky, Jennifer; Viveky, Navita; Cheng, Pui Chi; Almousa, Ahmed; Hadjistavropoulos, Thomas; Alcorn, Jane
ABSTRACT: Evidence from the literature suggests that dietary flaxseed lignans have the ability to modulate inflammation, which is recognized as the underlying basis of multiple chronic human diseases in older adults. Our objective was to determine the effects of oral lignan supplementation on biochemical and functional indicators of inflammation as well as safety and tolerability in older healthy adults. We designed a randomized, double-blind, placebo-controlled clinical trial in older healthy adults (60–80 years) to assess flaxseed lignan–enriched complex (∼38% secoisolariciresinol diglucoside [SDG]; 600 mg SDG dose) oral supplementation effects on biochemical and functional indicators of inflammation and safety and tolerability in older healthy adults after 6 months of once-daily oral administration. The clinical trial confirmed that plasma concentration of total flaxseed lignans (free and conjugated forms) secoisolariciresinol (SECO), enterodiol (ED), and enterolactone (ENL) were significantly associated with daily oral supplementation of flaxseed lignan–enriched complex ( p < 0.05). A significant decrease in systolic blood pressure (SBP; from a mean of 155 ± 13 mm Hg at baseline to 140 ± 11 mm Hg at 24 weeks) was observed in lignan-supplemented participants stratified into an SBP ≥140 mm Hg subcategory ( p = 0.04). No differences were found between treatment or placebo groups in terms of cognition, pain, activity, physical measurements (calf, waist, and upper arm circumstances), and grip strength. With respect to blood inflammatory markers, lipid profiles, and biochemical parameters, no significant differences were found between treatment and placebo groups at the end of the 6-month supplementation. No adverse effects were reported during supplementation. These data further support the safety and tolerability of long-term flaxseed lignan–enriched complex supplementation in older adults and identify an ability to favorably modulate SBP, an important risk factor in cardiovascular disease.